Analisis Proses Pembuatan Arang Dan Asap Cair Pada Insineraor Ramah Lingkungan - Anggraini, Mardeli; Azriadi, Emon; Yona Sidratul Munti , Novi; Kumala Sari , Resy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
Garbage in Indonesia is very dangerous for people's lives. In 2019, Indonesia produced 66-67 million tons of waste (Rhohman & Ilham, 2019). The development of industry in Indonesia is currently growing very rapidly and has penetrated into various sectors, so it will be followed by the demand for various kinds of industrial raw materials both at home and abroad, one of which is in waste management using incinerators that produce charcoal and smoke. fluid. This study aims to determine which fuels burn optimally and which fuels can slightly reduce waste. The type of research used in this research is descriptive research by utilizing an incinerator to produce charcoal and liquid smoke. Based on the results of the test data obtained, it shows that charcoal that uses wood as raw material is burned using more waste than using shells as raw material. So that by using wood raw materials can slightly reduce the existing waste.